2019
DOI: 10.1007/s10815-019-01502-0
|View full text |Cite
|
Sign up to set email alerts
|

Human OVGP1 enhances tyrosine phosphorylation of proteins in the fibrous sheath involving AKAP3 and increases sperm-zona binding

Abstract: Purpose To investigate if the recombinant human oviduct-specific glycoprotein (rHuOVGP1)–enhanced tyrosine-phosphorylated (pY) proteins are components of specific structure(s) of the sperm tail and if rHuOVGP1 binds to the oocyte and enhances sperm-egg binding. Methods Immunofluorescent staining and confocal microscopy were performed to examine the localization of pY proteins, outer dense fiber (ODF), and A-Kinase Associated Protein 3 (AKAP3) in human sperm during capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…KO males were completely sterile. phological defects and characterized by sperm flagella which are short, coiled, irregular, or even absent-has been associated with a variety of genes in humans and in mice (e.g., AKAP3, AKAP4, AK7, CCDC39, DNAH1, CFAP43, CFAP44, CFAP69, CFAP65, CFAP70, CFAP251, SPATA6, TE KT4, TSSK4, ODF2, ROPN1, FSIP2, TTC21A, and QRICH2) [3,7,[13][14][15][16][17][18][19][20][21][22][23][24][25]27,32,33]. The increasingly large number of such genes emphasizes the extensive genetic heterogeneity of MMAF, strongly suggest that more genes remain to be identified for MMAF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KO males were completely sterile. phological defects and characterized by sperm flagella which are short, coiled, irregular, or even absent-has been associated with a variety of genes in humans and in mice (e.g., AKAP3, AKAP4, AK7, CCDC39, DNAH1, CFAP43, CFAP44, CFAP69, CFAP65, CFAP70, CFAP251, SPATA6, TE KT4, TSSK4, ODF2, ROPN1, FSIP2, TTC21A, and QRICH2) [3,7,[13][14][15][16][17][18][19][20][21][22][23][24][25]27,32,33]. The increasingly large number of such genes emphasizes the extensive genetic heterogeneity of MMAF, strongly suggest that more genes remain to be identified for MMAF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different mutant mouse models have been developed to study the genetic and molecular causes of sperm developmental defects, yielding deep understanding regarding spermatogenesis [12]. Previous studies in human and mutant mouse models have investigated and identified several genes associated with flagella abnormalities including AKAP3, AKAP4, AK7, CCDC39, DNAH1, CFAP43, CFAP44, CFAP69, CFAP65, CFAP70, CFAP251, SPATA6, TEKT4, TSSK4, ODF2, ROPN1, FSIP2, R2D2, TTC21A and QRICH2 [3,4,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, the etiology of several genetic factors responsible for MMAF is still elusive as genetic mutation accounts for 60% of MMAF defects, mirroring the strong genetic heterogeneity which can occur with MMAF [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also showed the presence of oviductin, which is also in accord to previous studies where oviductin recruitment on the sperm membrane has been shown [ 62 ]. This protein is known to be present in OF from different species [ 38 , 80 ], such as pig, bovine, hamster, and human, where its binding to the head sperm plasma membrane was shown to have an important role inducing sperm capacitation [ 81 , 82 ]. Moreover, oviductin is involved in tyrosine phosphorylation of sperm proteins during in vitro capacitation, confirming its role in sperm fertility [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is known to be present in OF from different species [38,80], such as pig, bovine, hamster, and human, where its binding to the head sperm plasma membrane was shown to have an important role inducing sperm capacitation [81,82]. Moreover, oviductin is involved in tyrosine phosphorylation of sperm proteins during in vitro capacitation, confirming its role in sperm fertility [82,83]. Some of the proteins identified in spermatozoa incubated with OF or SP + OF belong to the heat shock proteins family, such as endoplasmin, heat shock cognate 71 kDa protein, 78 kDa glucose-regulated protein, and heat shock protein HSP 90-beta.…”
Section: Oviductal Fluid (Of)-sperm Protein Interactionmentioning
confidence: 99%
“…Lastly, the study from Bichara et al [4] sheds new light on deeper aspects, such as the impact of sperm nuclear damage on ICSI outcomes. To better characterize this negative effect, the authors examined clinical pregnancy rates after ICSI according to several types of sperm DNA damage (sperm head vacuoles, chromatin condensation, DNA fragmentation, and aneuploidy) that were explored simultaneously in 132 couples with male factor or mixed infertility.…”
mentioning
confidence: 99%